2007
DOI: 10.5089/9781451866223.001
|View full text |Cite
|
Sign up to set email alerts
|

A Primeron Sovereign Debt Buybacks and Swaps

Abstract: This Working Paper should not be reported as representing the views of the IMF.The views expressed in this Working Paper are those of the authors and do not necessarily represent those of the IMF or IMF policy. Working Papers describe research in progress by the author(s) and are published to elicit comments and to further debate. This paper sets forth some basic principles that could help debt managers in emerging market and other countries to plan and implement sovereign debt buyback and swap operations. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The allegation that has received the most attention from attorneys on both sides of the litigation nationwide, however, is that nonprofit hospitals entered into an express and/or implied contract with the United States requiring them to "provide mutually affordable medical care ... in return for substantial federal, state and local tax exemptions."' In particular, the Yale suit notes tax exemptions under 26 USC 501(c)(3) and Conn. Gen. Stat. 5…”
Section: Factual Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The allegation that has received the most attention from attorneys on both sides of the litigation nationwide, however, is that nonprofit hospitals entered into an express and/or implied contract with the United States requiring them to "provide mutually affordable medical care ... in return for substantial federal, state and local tax exemptions."' In particular, the Yale suit notes tax exemptions under 26 USC 501(c)(3) and Conn. Gen. Stat. 5…”
Section: Factual Backgroundmentioning
confidence: 99%
“…25 The company also conducted "extension studies" of studies 329 and 701, which specifically focused on safety rather than efficacy. 26 According to the State of New York, studies 377 and 701 failed to show that paroxetine was more effective than a placebo, while study 329 presented a mixed picture of paroxetine's effi~acy.~7 Additionally, the three original studies suggested that potentially suicidal behavior was two times more likely in the paroxetine group than in the placebo group, and the extension studies supported these findings. 28 The complaint alleged that GlaxoSmithKline attempted to suppress and misrepresent the studies' findings on several leveh29 First OK the company permitted the study with ambiguous results, study 701, to be published, but did not release the results of studies 377 and 701 or the extension studies.30 Secondly, the complaint asserted that GlaxoSmithKline misrepresented the safety and efficacy outcomes to its drug representatives, tacitly encouraging the reps to distribute the information to phy~icians.3~ The complaint cites an internal memo to all sales representatives selling Paxil, which stated: "Paxil demonstrates REMARKABLE Efficacy and Safety in the treatment of adolescent depre~sion.…”
Section: Introductionmentioning
confidence: 99%